Characterisation and asymmetry analysis of rainfall distribution associated with tropical cyclones over Bay of Bengal : NISHA (2008), LAILA (2010) and JAL (2010) - BALACHANDRAN, S.; GEETHA, B. (MAUSAM, 2014)
The precipitation characteristics and spatial rainfall asymmetry in respect of three tropical cyclones (TCs) of Bay of Bengal, viz., NISHA (2008), LAILA (2010) and JAL(2010) that affected coastal Tamil Nadu are studied using TRMM based rain rate data. The analysis is carried out by dividing the life cycle of the TC into various stages of intensification and weakening. Percentage frequency distribution, radial profile and quadrant-wise mean rain rates are determined stage-wise for each TC. Further, spatio-temporal variations in the rainfall asymmetry is studied using Fourier analysis by computing the first order wave number-1 asymmetry around the TC centre. The results indicate a shifting of higher frequency rain rates from higher to lower rain rate side when the TC passes from intensification to weakening stages. The azimuthally averaged mean rain rates indicate a peak rain rate of 4-5 mm/hr over 50-100 km from the TC centre during intensification stages which decreases to a very low rate of about 1 mm/hr during the final stages of weakening. For the same intensity category, the radial profiles of mean rain rates show marked difference between the intensification and weakening stages. The quadrant mean rain rates show large asymmetries in the radial rainfall distribution with more rainfall concentrated in front left quadrant during the stages of intensification. Such TC rainfall asymmetries are shown to be influenced by the environmental vertical wind shear and translational speed of the TC. When the wind shear and storm motion vectors are in the same direction, a dominant down shear left asymmetry is observed. Evolution of wave number-1 asymmetry indicates that, by and large, asymmetry amplitude increases from the centre outwards and a cyclonic (anti-cyclonic) shift during the intensification (weakening) stages of the TCs.